A Single Nucleotide Polymorphism in SLC7A5 is Associated with Gastrointestinal Toxicity after High-Dose Melphalan and Autologous Stem Cell Transplantation for Multiple Myeloma - Giglia, Jennifer L. (2014)
Multiple myeloma is the most frequent indication for high-dose melphalan (HDM) chemotherapy with autologous stem cell transplantation (ASCT). Gastrointestinal symptoms represent the most significant non-hematological toxicity of HDM. However, specific, especially genetic, predictors of their incidence or clinical severity are lacking. The amino acid transporters LAT1 and LAT2 encoded by the SLC7A5 and SLC7A8 genes, respectively, are the principal mediators of melphalan uptake into cells. To determine whether genetic variability at these loci contributed to inter-individual differences in the development of gastrointestinal complications of HDM, we analyzed single-nucleotide polymorphisms (SNPs) in these genes in 135 patients with multiple myeloma treated with HDM and ASCT and need for total parenteral nutrition (TPN). Seven SNPs in SLC7A5 and twenty in SLC7A8 were genotyped. Multiple analyses indicated that one SNP in the first intron of SLC7A5, rs4240803, significantly associated with TPN use (OR= 0.45, 95% CI 0.25 – 0.79, p = 0.007). Further, every haplotype that correlated with TPN requirement incorporated this SNP. These results suggest that variability in melphalan transport impacts mucosal injury after HDM. This finding could help in individualizing the dose of this effective and widely used chemotherapeutic agent for multiple myeloma.